1989
DOI: 10.1021/ie00095a015
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of nickel and copper from the ammoniacal leach solution of sea nodules by LIX 64N

Abstract: pendent of product viscosity.6. In practice, the mass-transfer control aspects of flash devolatilization can be treated as an effective increase in vacuum, the magnitude of which is dependent on the component and the equipment design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Although this process has been extensively studied [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], quantitative studies of the equilibria are scarce. Flett and Melling [19] are the only investigators to have analyzed ammonia extraction; they showed good agreement between experimental results obtained with a -hydroxyoxime (LIX65N, 10 vol%) in an aliphatic diluent and the results obtained with a model that assumed the formation of a monomeric 1:1 extractant/ammonia adduct.…”
Section: Introductionmentioning
confidence: 99%
“…Although this process has been extensively studied [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], quantitative studies of the equilibria are scarce. Flett and Melling [19] are the only investigators to have analyzed ammonia extraction; they showed good agreement between experimental results obtained with a -hydroxyoxime (LIX65N, 10 vol%) in an aliphatic diluent and the results obtained with a model that assumed the formation of a monomeric 1:1 extractant/ammonia adduct.…”
Section: Introductionmentioning
confidence: 99%
“…Ammoniacal ammonium carbonate solution has been widely used in the leaching of metals like nickel, copper, cobalt, iron, silver, manganese, and zinc from ores [5][6][7]. The leaching system is usually made by a reaction between metal ore and ammonium carbonate in ammonia solution [8-4 10].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative and effective way to achieve the goal is resorted on the combinations of commonly available commercial reagents [15]. Large amounts of extraction system integrated with more than one extractant type have been reported for selective recovery of metals from various solutions [16][17][18][19], including various commercialized products, such as LIX984N [20], LIX64N [21,22], LIX973 [23,24], and so on. Based on the synergistic system of Cyanex272 and PC-88A, Liu et al proposed a feasible separation process for recovery and separation of Mn, Cu and Co from the leachate of waste lithium ion batteries [18].…”
Section: Introductionmentioning
confidence: 99%